An Integrated Model for Managing Land Contaminated with Mercury due to Small-Scale Gold Mining in Lebak Regency, from the Perspective of Regional Development - Djoko Santoso Abi Suroso; Roos Akbar; Dewi Sawitri Tjokropandojo; Tubagus Furqon Sofhani (The Directorate for Research and Community Services, Institut Teknologi Bandung, 2022)
Managing land contaminated with mercury due to artisanal small-scale gold mining (ASGM) in Indonesia generally follows an engineering approach. Meanwhile, there is a high level of community dependence on the contaminated land and the gold mining activities using mercury, directly and indirectly. Therefore, an engineering approach cannot solve the complex problem of managing mercury in Indonesia. Moreover, engineering approaches do not address the root problems of ASGM, i.e., poverty and the need for jobs that offer a higher income than agriculture. The implication of this is that the implementation of land restoration may not succeed without a comprehensive study of socio-economic and regional aspects. This is because of the chance that communities will reject the transition from mercury-based livelihoods. To deal with this problem, this study assessed the management of mercury using a transdisciplinary approach and participatory action research (PAR), involving multi-disciplinary experts in developing mercury restoration plans based on an integrated model that considers engineering, socio-economic, regional, and legal aspects. The empirical part of this study was based on a survey in Lebak Regency, one of the regions in Indonesia with the most mercury contamination. The comprehensive research produced a plan for social change, a mercury-free economic plan, and policy recommendations.